A presença da fenomenologia na educação física brasileira: Implicações para o estudo do corpo e outras problematizações - Quintão de Almeida, Felipe (2013)
This paper discusses the uses of phenomenology in Physical Education in Brazil. In methodological terms, it describes five studies that belong to this theoretical framework in the field, represented by authors such as Silvino Santin, Manuel Sérgio, Wagner Wey Moreira, Elenor Kunz and Terezinha Petrúcia da Nóbrega. It problematizes some aspects of this reception, by highlighting not only its boundaries, but also the challenges for research and reflection within this tradition in physical education